Study on the Relationships among Marketing Information System Quality and Brand Equity Management in Banking Sector - Ali, Mohamed Salih Yousif (Asian Business Review, 2015)
Marketing information system plays critical role in improving brand power and long-term profitability. The purpose of this study was to investigate the relationship between marketing information system quality (MKISQ) and brand equity management (BEM) within the banking sector. Results show that the three components of the MKISQ: marketing information quality, marketing support service quality, and marketing orientation quality Influence brand equity. This study contributes to the theoretical and managerial implication empirical of the MKISQ and BEM. The paper provides detail discussion, Imitations and suggestions for future research.
Keywords: Marketing system quality; brand equity; Banking Sector